Comparative Fate of Chemically Dispersed and Beached Crude Oil in Subtidal Sediments of the Arctic Nearshore - Boehm, P.D.; Steinhauer, M.S.; Green, D.R.; Fowler, B.; Humphrey, B.; Fiest, D.L.; Cretney, W.J. (ARCTIC, 1987)
A three-year investigation was conducted to examine the incorporation of petroleum hydrocarbons (PHC) into subtidal sediments following experimental releases of oil during the Baffin Island Oil Spill (BIOS) Project experiments. The concentrations of PHC were determined by synchronous scanning UV/Fluorescence spectroscopy, while the composition of residual saturated and aromatic hydrocarbons was determined by gas chromatography and gas chromatographic mass spectrometry. . The eroding oil from the Bay 11 beach was compositionally quite heterogeneous, with weathered, biodegraded oil, as well as relatively unweathered oil, found on the beach and in the offshore sediments. Biodegradation of oil appeared to be restricted to the beached oil, with no significant degradation apparently occurring subtidally. After two years, the offshore oil residues still contained low molecular weight alkanes as well as alkylated naphthalenes. The situation in Bay 9, where chemically dispersed oil was discharged near the bottom, was quite different. In spite of a large water column exposure, the bottom sediments never contained more than 10 micro g/g of oil. Of this amount of oil, a significant fraction (20%) of the PHC was initially associated with the surface flocculent layer. Levels of oil in the Bay 9 sediments were on the order of 1-3 micro g/g one year after the release. Sediment PHC levels in the other less exposed bays (Bays 10 and 7) never exceeded 3 micro g/g.Key words: BIOS, experimental oil spill, petroleum hydrocarbons, arctic sediments, oil pollution Mots clés: BIOS, déversement de pétrole expérimental, hydrocarbures pétroliers, sédiments arctiques, pollution par le pétrole